Acute kidney injury among HIV-infected patients admitted to the intensive care unit. (November 2015) - Randall, DW; Brima, N; Walker, D; Connolly, J; Laing, C; Copas, AJ; Edwards, SG; Batson, S; Miller, RF
We describe the incidence, associations and outcomes of acute kidney injury (AKI) among HIV-infected patients admitted to the intensive care unit (ICU). We retrospectively analysed 223 admissions to an inner-London, University-affiliated ICU between 1999 and 2012, and identified those with AKI and performed multivariate analysis to determine associations with AKI. Of all admissions, 66% were affected by AKI of any severity and 35% developed stage 3 AKI. In multivariate analysis, AKI was associated with chronic kidney disease (odds ratio [OR] = 3.19; p  = 0.014), a previous AIDS-defining illness (OR = 1.93; p  = 0.039) and the Acute Physiology and Chronic Health Evaluation (APACHE) II score, (OR = 3.49; p  = 0.018, if > 30). No associations were demonstrated with use of anti-retroviral medication (including tenofovir), or an individual's HIV viral load or CD4 count. AKI was associated with higher inpatient mortality and longer duration of ICU admission. Among patients with stage 3 AKI, only 41% were alive 90 days after ICU admission. Among survivors, 74% regained good renal function, the remainder were dependent on renal replacement therapy or were left with significant ongoing renal dysfunction. Of note, many patients had baseline serum creatinine concentrations well below published reference ranges. AKI among HIV-infected patients admitted to ICU carries a poor prognosis.